Anti Dumping as a Trade Remedy Under the WTO Regime: Experience of Pakistan - Naeem Ullah Khan (Journal of Political Studies, 2016)
Economic interest of nations frequently clash and trade conflicts among them do arise. Un-restricted and flow trade, business and commerce activities between different nations is alleged in global Market, as means to economic growth and betterment of living standard in way to a happier situation of human survival. For aggrieved persons there are some essential trade remedies. For trade remedial measures there are options in form of WTO agreements. The WTO agreements provide to have recourse to trade remedial measures. In this context Pakistan has promulgated the Anti- Dumping Ordinance to stop the unfair trade and to protect the interest of stake holders. To determine and investigate the local injury towards the domestic industry, the law provides the tool for it. The purposed project establishes the relationship between Dumped products and its affect on economic growth and trade.